GRUPO DE ESTUDOS E DESENVOLVIMENTO WEB - Celmer, Alex Jung; Frey, Daniel; Sebastiany, Felix Hoffmann; Cardoso, Gabriel Alexander; Hein, Paulo Henrique; Felber, Wiliam (Salão do Conhecimento, 2019)
Projeto de extensão realizado no grupo de estudo do Câmpus Santa Rosa - Unijuí.